Direct synthesis of hydrogen peroxide from hydrogen and oxygen: an overview of recent developments in the process - Samanta, Chanchal (Applied Catalysis A-General, 2008)
Hydrogen peroxide (H(2)O(2)) is an important commodity chemical and its demand is growing significantly in the chemical synthesis due to its ``green'' character. Currently, H(2)O(2) is produced almost exclusively by the anthraquinone auto-oxidation (AO) process. The AO process involves indirect oxidation of hydrogen and thus avoids potentially explosive H(2)/O(2) mixture. However, this large-scale process presents significant safety issues associated with the transport of bulk H(2)O(2). Moreover, the AO process can hardly be considered ail environmentally friendly method. In view of this, more economical and environmentally cleaner routes have been explored for the production of H(2)O(2). The liquid-phase catalytic direct synthesis of H(2)O(2) from H(2) and O(2) offers an attractive green technology for small-scale/onsite production of H(2)O(2). However, the direct synthesis process suffers from two major drawbacks: (i) potential hazards associated with H(2)/O(2) mixtures and (ii) poor selectivity for H(2)O(2) because the catalysts used for H(2)O(2) synthesis are also active for its decomposition and hydrogenation to water as well as for H(2) combustion. These serious issues and the recent developments in the direct H(2)O(2) synthesis are discussed in this review. The roles of protons (H(+)) and halide ions in promoting the H(2)O(2) selectivity are also examined in detail. (C) 2008 Elsevier B.V. All rights reserved
Keywords: Bimetallic catalysts; Direct H(2)O(2) synthesis; Microreactor technology; Pd catalysts